Effect of the contact tank geometry on disinfection efficiency. (June 2021) - Bruno, P.; Di Bella, G.; De Marchis, M.
Abstract: Disinfection is a sanitary treatment present in both drinking water and wastewater treatment plants aimed at removing pathogenic microorganisms able to damage the human health. The focus of this study is to apply Computational Fluid Dynamics (CFD) to study and to improve the disinfection efficiency through the optimization of the hydrodynamics inside the disinfection tank. Numerous literature studies have shown that water flow inside traditional multichamber tanks is highly turbulent because of the development of large as well as small vortices in which flow velocity decreases or even vanishes (dead zones). These turbulent phenomena are responsible of an increase of the real residence time, compared to the theoretical one, causing poor disinfection and the development of unwanted by-products. In the present analysis, Large Eddy Simulation (LES) is used to simulate three-dimensional turbulent flow and disinfectant transport in different contact tanks using a structured finite-volume discretization. The results show how the baffles' geometry, as well as the design of technical and construction details, influences the hydraulic retention time of the disinfectant, varying the disinfection efficiency. In particular, the creation of horizontal baffles inside the vertical baffle chambers reduces the free space and extends the flow path. This reduces both short circuits and recirculation zones bringing the flow closer to the ideal plug-flow condition.